Pengembangan Sistem Informasi Penggajian Karyawan Bus Pariwisata PT. Mahkota Mitra Sentosa Menggunakan Metode Rational Unified Process (RUP) - Tedja Adhi Putra; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Mahkota Mitra Sentosa is a service company that runs in land transportation especially tour bus. On the payroll process for driver, assistant, and the final report of the calculation is still using conventional method. This causes an issue of time inefficiency in the process. In the calculation process, sometime it is needed to recalculate to make sure that the previous calculation is correct. The problems exist need a solution which is developing an information system. This study explains how to develop an information system needed by Pt. Mahkota Mitra Sentosa to resolve the existing problems by using system development method which is Rational Unified System. The method is an object-based development system by several steps which are: inception, elaboration, construction, and transition. This method is used because it can do the process iteratively to accommodate the change of need. The result of this study is a web-based information system. The developed information system is tested by using black-box testing generated valid values in all test cases. Compatibility testing is used to test non-functional requirements with the results of several minor issues. User Acceptance Testing generated a final value of 87.2%. In the end, it can be deduced that the information system has been built properly and in accordance with the needs. Finally, it is concluded that the information system has been well-developed and corresponded the need.